Betting Against Moral : European Evidence - Kärnä, Juha (My University, 2020)
This thesis investigates possibility to generate abnormal returns on the European market, by investing against general moral and ethical opinions. A substantial amount of academic literature suggests there to be a connection between industries that are considered to be sinful such as tobacco-, alcohol- and gambling industries and abnormal returns (see e.g. Richey, 2017; Hong and Kacperczyk, 2009). Controversially, academic literature on the Social Responsible Investment strategies have provided contradictory results between high ESG-rated stocks and abnormal returns (see e.g. Bazo et al., 2010; Halbritter and Dorfleit-ner, 2015. Utilizing financial data from Datastream, ESG values obtained from the Thomson Reuters ASSET4 database and factor-data from Kenneth R. French data-base, this thesis attempts to investigate the financial performance of sin stocks and SRI in Europe. The thesis uses stock information from 18 different European countries, applying the Fama and French (2015) three-factor model, Fama and French (2018) six-factor model and Capital Asset Pricing Model, to construct long-short portfolios by going long on morally doubtful sin stocks and shorting ethical ESG stocks. In order to research the impact of sin stocks and SRI, the thesis constructs two separate long-short portfolios by the frequency of the sinful industry is used in relevant academic research. This research concludes that investing in the sin stocks outperforms the market with significant result, but shorting ESG stocks does not provide additional abnormal return for investor. Using a research period of 15 years for stock returns from January 2003 to December 2018 and ESG-data from December 2002 to December 2017, this thesis finds that over the whole research period, sin stocks overperforms both market and ESG stocks, but since ESG stocks overperform the overall market, shorting the ESG stocks will not increase the abnormal return by constructing the long-short portfolio. Research find that broader sin portfolio including all the industries considered sinful, outperform the narrower sin portfolio
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance